Micro-grid optimization scheduling method and device, electronic equipment and storage medium - YI YANG; XU ZHANPENG; MIAO LU; CHEN KUIYE; YANG CHENG; GU YICAN; ZHANG XINGZI; LIU HAOYI; YANG ZHENNAN (2025)
The invention discloses a micro-grid optimization scheduling method and device, electronic equipment and a storage medium. The method comprises the steps of obtaining an energy transaction parameter, a user electricity purchase parameter, a user gas load and a user thermal load of a micro-grid operator; constructing a user game model according to the time-sharing coupling electricity carbon price and the user electricity purchasing parameter at each moment; solving the user game model, and generating the actual electricity purchase quantity of the user at each moment; constructing a micro-grid operator game model according to the actual electricity purchase quantity of the user at each moment, the user gas load, the user heat load and the energy transaction parameters of the micro-grid operator; solving the micro-grid operator game model, and generating the electricity purchase quantity of the micro-grid operator at each moment, the gas purchase quantity of the micro-grid operator at each moment, the energy p